2009
DOI: 10.1007/s00439-009-0626-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of susceptibility genes for complex diseases using pooling-based genome-wide association scans

Abstract: The success of genome-wide association studies (GWAS) to identify risk loci of complex diseases is now well-established. One persistent major hurdle is the cost of those studies, which make them beyond the reach of most research groups. Performing GWAS on pools of DNA samples may be an effective strategy to reduce the costs of these studies. In this study, we performed pooling-based GWAS with more than 550,000 SNPs in two case-control cohorts consisting of patients with Type II diabetes (T2DM) and with chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 36 publications
(46 reference statements)
1
82
0
5
Order By: Relevance
“…DNA pooling has been originally used as an economic and alternative tool for genotyping and GWAS; therefore, it can be applied to discover common CNVs in certain studies [30,31]. However, the copy number estimation represents a challenge in terms of false-positive rates, so it has been suggested that CNVs identified from SNP genotyping data must always be validated with an alternative method to avoid erroneous calls [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA pooling has been originally used as an economic and alternative tool for genotyping and GWAS; therefore, it can be applied to discover common CNVs in certain studies [30,31]. However, the copy number estimation represents a challenge in terms of false-positive rates, so it has been suggested that CNVs identified from SNP genotyping data must always be validated with an alternative method to avoid erroneous calls [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, the copy number estimation represents a challenge in terms of false-positive rates, so it has been suggested that CNVs identified from SNP genotyping data must always be validated with an alternative method to avoid erroneous calls [31,32]. A past study with schizophrenia in Brazilian samples also used pooling strategy to evaluate the CNVs and the possible role in the disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results obtained with this type of stratification may reflect only the allelic distribution for each pool, which is of importance to determine whether any significant differences exist between the populations under study. However, pooling methodology does not exclude the use of individual genotyping to develop association studies (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is also a very useful tool for genome-wide association studies (GWAS), as it allows allelic frequency estimation, rather than specific genotypes, allowing for analysis and the classification of the likelihood of association with a disease. The development of this technique in GWAS studies allows cost savings which are essential in studies of this size (31).…”
Section: Discussionmentioning
confidence: 99%
“…An even cheaper approach is to employ DNA-pooling [34] . This means that the DNA samples from several individuals are pooled together and subsequently used for genotyping.…”
Section: Genotyping Chipsmentioning
confidence: 99%